Surface treatment method
The surface treatment method addresses the challenge of reducing friction and wear by using laser-activated particle collisions to form deep, sparse impressions, achieving superior friction reduction and wear suppression in mechanical devices.
Patent Information
- Application Number
- JP2023103507
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-23
- Publication Date
- 2025-01-09
AI Technical Summary
Existing surface treatment techniques fail to adequately reduce surface frictional resistance and suppress wear in mechanical devices, despite the increasing demand for extended lifespan and reduced energy consumption.
A surface treatment method involving the placement of particles on an energy absorption layer, irradiating the layer with a laser beam to eject particles, causing them to collide with the object to be treated, forming depression-shaped impressions that reduce friction and wear.
The method effectively reduces surface frictional resistance and suppresses wear by creating sparse, deep indentations that retain lubricant, enhancing the durability and reducing frictional resistance beyond conventional methods.
Smart Images

Figure 2025003051000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a surface treatment method. [Background technology]
[0002] For example, in devices and parts that experience friction and sliding contact, such as bearings and gears of rotating bodies in mechanical devices, it is necessary to reduce the frictional resistance of the surface and suppress wear. By reducing the frictional resistance of the surface and suppressing wear, it is possible to extend the life of mechanical devices and parts and reduce energy consumption. One example of a technology that can reduce the frictional resistance of a surface and suppress wear is a surface treatment technology that forms irregularities on the surface, such as shot peening.
[0003] Patent Document 1 discloses a micro laser peening process using powder and coating, and a micro laser peening-treated part. In this micro laser peening process, powder and coating of resin, metal, ceramics, lubricant, hardener, etc. are attached to the surface of various metal materials and resin parts as the workpiece, and then a laser absorption enhancement coating is provided on top of it. Then, a laser interference film is formed on top of it, and a short pulse high peak output laser is focused on top of it to perform laser peening. In this micro laser peening process, fine depressions are formed on the surface of the workpiece, and lubricant oil is accumulated in the depressions, thereby improving lubricity, sliding properties, and wear resistance. In addition, a modified layer in which foreign powder is embedded in the surface layer is formed on the surface treated by this micro laser peening process. As a result, the surface layer is modified by introducing a large compressive residual stress, expanding the surface area, hardening the structure, finer structure, and eliminating cavities just below the surface.
[0004] Patent Document 2 discloses a surface treatment method for steel products. In this surface treatment method, roughly spherical blast particles with a median diameter d50 of 1 to 20 μm are blasted into a treatment area of the steel product, which is a region where surface treatment is to be performed, together with compressed gas at a blast pressure of 0.01 MPa to 0.7 MPa, to perform shot peening so that the coverage of the treatment area is 50% or more. It is said that this surface treatment method can significantly improve the wear resistance and fatigue strength of the steel product by increasing secondary carbides near the surface of the steel product, reducing voids (gaps), and nano-crystallizing crystal grains. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2006-320907 A [Patent Document 2] JP 2018-199843 A Summary of the Invention [Problem to be solved by the invention]
[0006] Due to the recent growing interest in environmental and energy issues, there is a demand for longer life for machinery and parts and a reduction in energy consumption. Therefore, there is a demand for a surface treatment technology that can reduce surface friction resistance and suppress wear more effectively than conventional technologies.
[0007] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a surface treatment method that realizes reduction in frictional resistance and suppression of wear on the surface. [Means for solving the problem]
[0008] In order to achieve the above object, the surface treatment method according to the present disclosure is as follows.
[0009] [1] A step of arranging particles on a surface of an energy absorbing layer; an ejection step of ejecting the particles by irradiating a rear surface of the energy absorbing layer with laser light; a flying step of flying the ejected particles toward a processing object; and a collision step of causing the flying particles to collide with the object to be treated.
[0010] [2] The surface treatment method according to the above-mentioned [1], wherein in the ejection step, a laser beam is irradiated onto the energy absorbing layer to generate a shock wave, and the particles are ejected by the shock wave.
[0011] [3] In the disposing step, a plurality of the particles are disposed on a surface of the energy absorbing layer; In the ejection step, a plurality of the particles are ejected, The surface treatment method according to the above-mentioned [1] or [2], wherein in the collision step, a plurality of the particles are collided with the treatment object.
[0012] [4] The surface treatment method according to any one of [1] to [3] above, wherein the ejection step, the flying step, and the collision step are repeated while changing a position at which the particles are collided with the treatment object in the collision step.
[0013] [5] The surface treatment method according to any one of [1] to [4] above, wherein in the collision step, the particles collided with the object to be treated form depression-shaped impressions on the surface of the object to be treated.
[0014] [6] The surface treatment method according to the above [5], wherein the indentation has a depth greater than 0.1 times the diameter of the opening.
[0015] [7] The surface treatment method according to [5] or [6] above, wherein in the collision step, the particles are collided with the object to be treated so that a protruding valley depth on the surface of the object to be treated is 1 μm or more.
[0016] [8] The surface treatment method according to any one of the above [1] to [7], wherein the particles are zirconia, tungsten or high speed steel.
[0017] [9] The surface treatment method according to any one of [1] to [8] above, wherein the particle diameter of the particles is 15 μm or more and 40 μm or less. Effect of the Invention
[0018] According to the surface treatment method of the present invention, it is possible to reduce the frictional resistance of the surface and suppress wear. [Brief description of the drawings]
[0019] [Figure 1] 1 is a diagram showing a schematic configuration of a surface treatment apparatus according to an embodiment of the present invention; [Diagram 2] FIG. 2 is an explanatory diagram of an ejection unit, an object to be processed, and ejection of particles. [Diagram 3] 2 is an enlarged optical microscope photograph of the treated surface of the surface treatment region according to Example 1. [Figure 4] 1 is a magnified optical microscope photograph of indentations in a treated surface according to Example 1. [Diagram 5] 4 is an enlarged optical microscope photograph of a shot peening treated surface according to Comparative Example 1. [Figure 6] 1 is an enlarged optical microscope photograph of a treated surface according to Comparative Example 2. [Figure 7] 1 shows measured cross-sectional curves of the treated surfaces of Example 1 and Comparative Examples 1 and 2. [Figure 8] 1 shows load curves of the treatment surfaces of Example 1 and Comparative Examples 1 and 2. [Figure 9] 1 is a bar graph comparing the protruding valley depths of the treated surfaces of Example 1 and Comparative Examples 1 and 2. [Figure 10] 1 is a bar graph comparing the level difference of the core portion of each treated surface of Example 1 and Comparative Examples 1 and 2. [Figure 11] 1 is a graph showing the results of a friction test on the treated surface of Example 1. [Figure 12] 1 is a graph showing friction test results for an untreated surface. [Figure 13] 1 is a bar graph comparing the average coefficient of friction of each of the treated and untreated surfaces of Example 1 and Comparative Examples 1 and 2. [Figure 14] 1 is a bar graph comparing the time to onset of seizure wear on the treated and untreated surfaces of Example 1 and Comparative Examples 1 and 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] Hereinafter, a surface treatment method according to an embodiment of the present invention will be described.
[0021] First, an outline of the surface treatment method according to the present embodiment will be described.
[0022] The surface treatment method according to this embodiment includes an arrangement step of arranging particles on the surface of the energy absorbing layer, an ejection step of irradiating the rear surface of the energy absorbing layer with laser light to eject particles, a flight step of causing the ejected particles to fly toward a treatment object, and a collision step of causing the flying particles to collide with the treatment object.
[0023] In the ejection step, the energy absorbing layer is irradiated with laser light to generate shock waves, and the particles are ejected by the shock waves.
[0024] In the collision step, the particles collide with the object to be treated to form depression-shaped impressions on the surface of the object to be treated.
[0025] According to the surface treatment method of this embodiment, it is possible to reduce the frictional resistance and suppress the wear of the surface.
[0026] Hereinafter, the surface treatment method according to the present embodiment will be described in detail with reference to the drawings.
[0027] 1 shows a schematic configuration of a surface treatment apparatus 100 (hereinafter referred to as the apparatus 100) according to this embodiment. The apparatus 100 includes an emission unit 1 that emits held particles P, and a light source 5 that is spaced apart from the emission unit 1 and emits laser light L toward the emission unit 1. An object 3 to be surface-treated is disposed spaced apart from the emission unit 1.
[0028] 1 and 2, the emission unit 1 has a support layer 11 formed of a light-transmitting material, and an energy absorbing layer 12 that receives laser light L and generates shock waves W. The emission unit 1 may be supported by a support (not shown) or the like in a state in which the position at which the laser light L is incident on the energy absorbing layer 12 is adjustable.
[0029] As shown in Fig. 2, the support layer 11 is a substrate that allows the laser light L to pass through and supports the energy absorbing layer 12. The support layer 11 is formed in a flat plate shape. The support layer 11 is formed of a light-transmitting material such as quartz glass or sapphire. There is no particular limit to the thickness d1 of the support layer 11. The thickness d1 of the support layer 11 is, for example, 500 µm or more and 2000 µm or less.
[0030] The energy absorbing layer 12 is an energy conversion mechanism that generates kinetic energy for making the particles P fly by receiving the laser light L. The energy absorbing layer 12 is disposed on one surface of the support layer 11. In the following description, the surface of the energy absorbing layer 12 that faces the support layer 11 is referred to as the back surface, and the opposite surface is referred to as the front surface.
[0031] For example, the energy absorbing layer 12 receives the laser light L, converts the energy supplied by the laser light L into heat, and rapidly evaporates itself by the heat, causing rapid expansion, thereby generating a shock wave W. The energy absorbing layer 12 ejects (flying) particles P by the shock wave W. The energy absorbing layer 12 can be arranged by layering on the surface of the support layer 11, for example, by applying a viscous fluid containing graphite and oil to the surface of the support layer 11. The energy absorbing layer 12 may include a layer of the viscous fluid arranged on the surface of the support layer 11, and a resin layer arranged on the layer of the viscous fluid (on the surface opposite to the side facing the support layer 11). For example, the thickness d2 of the energy absorbing layer 12 is 20 μm or more and 50 μm or less.
[0032] The processing object 3 is, for example, a flat plate. The processing object 3 is, for example, a metal plate. The processing object 3 may be disposed on an extension of the optical path immediately before the laser light L enters the energy absorbing layer. The processing object 3 may be supported by a support or holder with the surface of the processing object 3 (see FIG. 2) facing the support layer 11 of the emission unit 1. The processing object 3 is disposed at a predetermined distance from the emission unit 1. FIG. 2 illustrates an example in which the surface of the processing object 3 faces the support layer 11 of the emission unit 1 and is supported in parallel. The distance d3 between the processing object 3 and the emission unit 1 is, for example, 1 mm or more and 5 mm or less.
[0033] As shown in FIG. 1, the light source 5 irradiates the back surface of the energy absorbing layer 12 with laser light L from the support layer 11 side. The light source 5 may be any light source capable of irradiating the laser light L of a predetermined intensity for a predetermined time. The light source 5 may be, for example, an Nd-Yag laser light source, and may irradiate a laser pulse as the laser light L of a predetermined intensity and for a predetermined time. The light source 5 may be capable of outputting the laser light L with a pulse energy of 50 mJ or more (for example, 200 mJ), and may be capable of adjusting the pulse width within a range of 5 nm or more and 7 nm or less. As an example, the laser light L may be incident perpendicularly on the back surface of the energy absorbing layer 12.
[0034] The laser light L irradiated from the light source 5 may be irradiated linearly to the energy absorbing layer 12, or may be irradiated to the energy absorbing layer 12 via a reflecting device or a refracting device such as reflectors 51 and 52. The laser light L irradiated from the light source 5 may be irradiated to the energy absorbing layer 12 via a condenser lens 53 that focuses the light beam, as necessary. To explain this by taking a specific example, the laser light L irradiated from the light source 5 may be irradiated with a diameter of 6 mm from the light source 5, and then converged to a diameter of 400 μm by the condenser lens 53 before being irradiated to the energy absorbing layer 12.
[0035] The surface treatment of the treatment object 3 by the apparatus 100 is carried out as follows.
[0036] As shown in FIG. 2, the particles P are arranged by adhering to the surface of the energy absorbing layer 12 (an example of an arrangement process). A plurality of particles P may be arranged on the surface of the energy absorbing layer 12. Then, the light source 5 (see FIG. 1) is operated to irradiate the rear surface of the energy absorbing layer 12 with laser light L to emit the particles P (an example of an emission process). At this time, the laser light L is irradiated to a position on the rear surface of the energy absorbing layer 12 corresponding to the surface to which the particles P are attached. As a result, a shock wave W is generated in the energy absorbing layer 12, and the particle P near the point on the energy absorbing layer 12 where the laser light L is irradiated is emitted toward the processing object 3 by the shock wave. When a plurality of particles P are arranged at the position where the shock wave is generated by the laser light L entering the energy absorbing layer 12, a plurality of particles P are emitted toward the processing object 3.
[0037] The particles P projected toward the object 3 fly through the space between the energy absorbing layer 12 and the object 3 toward the object 3 (an example of a flying process), and then collide with the object 3 (an example of a collision process). When a plurality of particles P are projected toward the object 3, the plurality of particles P collide with the object 3.
[0038] When a particle P collides with the processing object 3, a recess, i.e., a depression-shaped indentation C (see FIG. 3) is formed on the surface of the processing object 3 due to the energy of this collision. When a plurality of particles P collides with the processing object 3, an indentation C corresponding to each particle P is formed on the surface of the processing object 3. When a plurality of particles P collides with the processing object 3, each indentation C is formed over a predetermined range (for example, within a circular area, hereinafter referred to as a unit processing range) on the surface of the processing object 3.
[0039] By repeating the ejection, flight, and collision of the particles P while changing the position at which the particles P collide with the treatment object 3, it is possible to form a plurality of indentations C over a wide range on the surface of the treatment object 3. For example, by sequentially forming unit treatment areas while changing the center position of the unit treatment area with some of the unit treatment areas overlapping, it is possible to form an area in which the indentations C are formed over a wide range on the surface of the treatment object 3, i.e., a surface-treated area.
[0040] The position where the particles P collide with the processing object 3 can be changed, for example, by moving the emission unit 1 and the holding unit 2 in a direction intersecting (for example, perpendicular to) the optical path of the laser light L while keeping the optical path of the laser light L fixed. In the present embodiment, as an example, the emission unit 1 and the holding unit 2 are both supported by a support unit and moved in a direction perpendicular to the optical path of the laser light L, thereby changing the position where the particles P collide with the processing object 3.
[0041] The surface-treated areas of the surface of the treatment object 3 have reduced surface friction resistance and are suppressed in wear.
[0042] An example of the particles P is a particle formed of zirconia, tungsten, or high speed steel. The high speed steel is a steel material specified in JIS G 4403:2022 (high speed tool steel material). By using the particles P formed of such materials as zirconia, tungsten, or high speed steel, it is possible to form an indentation C having a deeper depth relative to the opening diameter. By forming an indentation C having a deeper depth relative to the opening diameter, the frictional resistance of the surface-treated region is reduced more effectively, and the surface is more effectively suppressed in wear. It is preferable that the indentation C has a depth deeper than 0.1 times the opening diameter. This further enhances the effect of reducing the frictional resistance of the surface-treated region. It is not excluded that the particles P can be formed of other materials.
[0043] The particle diameter of the particles P is preferably, for example, 15 μm or more and 40 μm or less. When the particle diameter of the particles P is in this range, it is possible to form an indentation C having an opening diameter slightly smaller than these particle diameters (for example, 10 μm or more and 30 μm or more). By forming the opening diameter of the indentation C to correspond to this particle diameter, the friction resistance of the surface-treated area is reduced more effectively, and the surface is more effectively suppressed in wear. The particle diameter of the particles P may be a volume-based median diameter measured by a laser-type particle size measuring device. EXAMPLES
[0044] The surface treatment according to this embodiment will be described below based on examples.
[0045] Example 1 In this example, a stainless steel plate (made of SUS316L, 30 mm square, 3 mm thick, polished with #2000) was used as the treatment object. A surface treatment was performed by colliding monodispersed, spherical zirconia particles with a particle size (diameter) of 30 μm onto the plate. A device with the same configuration as the above-mentioned device 100 was used as the surface treatment device. This example will be described in detail below.
[0046] The energy absorbing layer was a tape (thickness: 30 μm) made of transparent PET film with a black acrylic adhesive (oil) containing graphite applied on one side. The side coated with the acrylic adhesive was placed opposite the plate surface of a support layer (thickness: 1.8 mm) made of quartz glass, and the energy absorbing layer was attached to the support layer to form the injection part.
[0047] The zirconia particles were then widely dispersed and attached to the surface of the energy absorbing layer. The amount of zirconia particles attached to the surface of the energy absorbing layer was about 500 particles / mm 2 From about 1000 pieces / mm 2 It was.
[0048] The light source used to emit the particles was capable of irradiating a Nd-Yag laser (wavelength: 1064 nm). The output of the laser light was 200 mJ with a pulse width of 6 nm. The laser light was converged by a condenser lens, and adjusted so that the diameter was 400 μm on the back surface of the energy absorbing layer when the support layer to which the energy absorbing layer was attached was placed in a predetermined position. The laser light was irradiated perpendicularly to the back surface of the energy absorbing layer.
[0049] The plate material to be treated was supported by the support part together with the injection part so as to be parallel to the energy absorbing layer of the injection part. It was placed at a position where the shortest distance from the surface of the energy absorbing layer (the surface opposite to the side facing the support layer) to the surface of the plate material (the surface to be treated, facing the energy absorbing layer) was 2.7 mm. The plate material was placed on the extension of the optical path just before the laser light was incident on the energy absorbing layer.
[0050] After the ejection unit, the light source, and the plate material were installed as described above, the cycle of ejection of zirconia particles by pulse irradiation of the laser light (200 mJ with a pulse width of 6 nm) onto the energy absorption layer, flight, and collision with the plate material (hereinafter simply referred to as the collision cycle), and the movement of the ejection unit and the holding unit in one direction by the support unit were repeated seven times, forming a belt-shaped area of the surface-treated treatment surface (hereinafter referred to as the surface treatment area) on the surface of the plate material. The moving speed of the zirconia particles during flight was about 350 m / s when measured by imaging with a high-speed camera. The surface treatment area was washed by pouring ethanol over it, and then further washed by pouring acetone over it, and was used for the subsequent evaluation.
[0051] In this embodiment, a circular area with a diameter of about 2 mm was formed on the treatment surface in one collision cycle. The above-mentioned Fig. 3 shows an enlarged optical microscope photograph of the treatment surface of the surface treatment region formed in one collision cycle in this embodiment. Note that Fig. 3 is an optical microscope photograph of the surface of the treatment object (taken with a microscope digital camera DP21 manufactured by Olympus Corporation, the same applies to the following optical microscope photographs).
[0052] The distance by which the support part moved the positions of the injection part and the holding part in one direction was 1 mm per movement. The surface treatment area formed after repeating a treatment cycle of one collision cycle and one movement seven times was a band-like shape as described above, with a width of 2.3 mm and a length of 8.4 mm.
[0053] 4 shows an enlarged optical microscope photograph of the indentation on the treated surface in the surface treatment region formed as described above. The indentation formed is a circle with a diameter of about 20 μm.
[0054] As shown in Figures 3 and 4, in the surface treatment region, the treatment surface is in a state where single circular indentations are sparsely arranged in a flat area. In the surface treatment region, overlapping of two or more indentations is hardly observed on the treatment surface. As shown in Figure 4, the depth of the formed indentations is deep.
[0055] Comparative Example 1 A shot peening treatment was performed on the same plate material as used in Example 1 to form a shot peened treated surface (hereinafter referred to as a shot peened treated surface). Fig. 5 shows an enlarged optical microscope photograph of this shot peened treated surface.
[0056] The shot peened surface has unevenness formed over the entire treated surface, with two or more overlapping indentations, as shown in Fig. 5. The indentations on the shot peened surface are shallower than the indentations on the treated surface in the surface treatment region of Example 1.
[0057] Comparative Example 2 The shot peened surface obtained in the same manner as in Comparative Example 1 was further polished to form a treated surface in which the convex portions of the shot peened surface were smoothed (hereinafter referred to as the smoothed surface). Fig. 6 shows an enlarged optical microscope photograph of this smoothed surface.
[0058] As shown in Fig. 6, the smoothed surface is a flat surface obtained by polishing the convex portions of the shot peened surface in Comparative Example 1. In the smoothed surface, concave portions formed by two or more overlapping indentations and smooth surface portions are formed over the entire treated surface. In the smoothed surface, concave portions formed by two or more overlapping indentations and flat surface portions are mixed together.
[0059] As can be seen by comparing the treated surface in the surface treatment region of Example 1 with the treated surfaces of Comparative Examples 1 and 2, the treated surface in the surface treatment region formed by the surface treatment method of this embodiment is unique in that it has single indentations sparsely formed thereon.
[0060] 7 shows the measured cross-sectional curves of the treated surfaces of Example 1 and Comparative Examples 1 and 2 formed as described above. The indentations of the treated surfaces of Comparative Examples 1 and 2 observed from the measured cross-sectional curves of Comparative Examples 1 and 2 are shallow, with a depth of about 1 μm. In contrast, the indentations of the treated surfaces in the surface treatment region observed from the measured cross-sectional curves of Example 1 have an opening diameter of about 20 μm and a depth of 3 μm to 5 μm, which is deep. The indentations of Example 1 have a depth of 0.15 to 0.25 times the opening diameter, which is deeper than 0.1 times the opening diameter.
[0061] The measured cross-sectional curve shown in Fig. 7 was measured using a scanning laser microscope (OLS4100, manufactured by Olympus Corporation) with an objective lens at 100x magnification. The measurement was performed over a linear range of 130μm in width. In the graph of Fig. 7, the vertical axis represents the height of the unevenness (μm) and the horizontal axis represents the position of the measurement target (μm).
[0062] Fig. 8 shows the load curves (so-called functional parameters) of the treated surfaces of Example 1 and Comparative Examples 1 and 2, and the surface (untreated surface) of the plate material to be treated. The load curve is a graph curve that expresses the ratio of the solid part of the surface unevenness in the height direction to the void part. In other words, the load curve is a curve that evaluates the degree of convexity and concavity on a certain surface part.
[0063] This load curve was obtained in accordance with ISO 25178. The measurement of the surface irregularities of each treated surface and untreated surface was conducted over a square area of 130 μm × 130 μm. Each load curve was obtained using the cutoff values of the S-filter and L-filter set for each measurement result of the treated surface and the untreated surface. The cutoff values of the S-filter and L-filter used for the measurement results of each treated surface and the untreated surface of Example 1 and Comparative Examples 1 and 2 are 1 μm and 150 μm, 1 μm and 250 μm, 1 μm and 350 μm, and 1 μm and 100 μm, in this order.
[0064] As can be seen from the load curve shown in Fig. 8, the treated surfaces of Comparative Examples 1 and 2 have a larger area occupied by convex portions than by concave portions, and the concave portions are shallow. In contrast, the treated surface of Example 1 has deep concave portions, and the area occupied by the concave portions is overwhelmingly larger than the area of the convex portions. Compared with the treated surfaces of Comparative Examples 1 and 2, the concave portions of the treated surface of Example 1 are deeper, and they occupy a larger area (larger area ratio). The planar portions (core portions) of the treated surface of Example 1 are flatter than the planar portions of the treated surface of Example 1.
[0065] Fig. 9 shows the protruding valley depth (Svk) of each treated surface and untreated surface of Example 1 and Comparative Examples 1 and 2, which was calculated based on the load curve shown in Fig. 8. Fig. 10 shows the level difference (Sk) of the core portion of each treated surface of Example 1 and Comparative Examples 1 and 2, which was calculated based on the load curve shown in Fig. 8. Note that the symbol N in Figs. 9 and 10 indicates the number of times data was acquired, and for example, "N=2" means that data was acquired twice.
[0066] As shown in Fig. 9, the protruding valley depth of the treated surface of Example 1 (3.09 µm) is more than five times deeper than the protruding valley depth of the treated surfaces of Comparative Examples 1 and 2 (0.54 µm and 0.50 µm, respectively). Therefore, when the treated surface of Example 1 is used as a sliding surface, it is easier to retain lubricant in the indentations as recesses, and frictional resistance can be reduced. The protruding valley depth of the untreated surface is 0.11 µm.
[0067] As shown in Fig. 10, the level difference of the core part of the treated surface of Example 1 (0.52 μm) is less than half of the level difference of the core part of the treated surfaces of Comparative Examples 1 and 2 (1.35 μm and 0.91 μm, respectively), and is therefore smoother. Therefore, when the treated surface of Example 1 is used as a sliding surface, the core part slides well with the lubricant, and the increase in frictional resistance due to the convex parts is suppressed, so that the frictional resistance (friction resistance) can be reduced. The level difference of the untreated surface is 0.11 μm.
[0068] The following describes the results of evaluating the friction coefficient by conducting a friction test on each treated surface of Example 1 and Comparative Examples 1 and 2 and the surface of the plate material to be treated (the surface that was not subjected to the surface treatment, hereinafter referred to as the untreated surface). The friction test was performed using a constant load tribo tester (manufactured by CSM Instruments, model: Tribometer), and the change in the friction coefficient over time was confirmed.
[0069] In this friction test, a 6mm diameter SUJ2 ball as specified in JIS G 4805 was used as the ball to be rubbed. In addition, in this friction test, 10μL of polyalphaolefin (PAO-4) was applied as a lubricant to the surface of each plate material to be evaluated (the surface to be subjected to the friction test) and then lightly wiped off with a paper towel. In this friction test, the load applied to the ball during friction was 10N, the friction stroke (the distance the ball was moved back and forth) was 5mm, the friction stroke speed was 3cm / s, and the maximum duration of the test was 30 minutes.
[0070] 11 and 12 show a graph of the friction test results of the treated surface of Example 1 (see FIG. 11) and a graph of the friction test results of the untreated surface (see FIG. 12). The horizontal axis of the graphs shown in FIG. 11 and FIG. 12 is the time (s) that the friction test continued, and the vertical axis is the friction coefficient.
[0071] 11 and 12, the friction coefficient in this test shows an indication of initial wear, that is, an increase in value at the beginning of the friction test, both for the treated surface of Example 1 and for the untreated surface. During the initial wear period, it is considered that phenomena such as abrasion of the treated surface of Example 1 and the untreated surface, particularly the convex parts, are worn away, causing significant generation of wear powder, and an increase in the friction coefficient (frictional resistance) are occurring.
[0072] After the initial wear period, the friction coefficient transitions to a steady wear state where it becomes approximately constant. During this steady wear period, the generation of wear powder decreases, and the friction coefficient (friction resistance) is reduced by the lubricant. The average value of the friction coefficient during the steady wear period (hereinafter, sometimes referred to as the average friction coefficient) is 0.139 for the treated surface of Example 1 and 0.178 for the untreated surface. Thus, the average friction coefficient is smaller for the treated surface of Example 1 than for the untreated surface. This is thought to be because the treated surface of Example 1 has deep indentations formed thereon, and therefore the lubricant is abundantly supplied from the indentations, resulting in a reduced friction coefficient (friction resistance) compared to the untreated surface.
[0073] In the case of the untreated surface, as shown in Figure 12, the friction coefficient started to increase again about 200 seconds after the start of the friction test. This increase in the friction coefficient is believed to be due to the occurrence of seizure wear. When seizure wear occurs, it is believed that the lubricant in the friction area has been completely consumed. It is also believed that no lubricant is being supplied from the surrounding area of the friction area.
[0074] In the case of the treated surface of Example 1, there was no sign of the friction coefficient increasing again during the duration of the friction test (30 minutes), as shown in Figure 11. That is, in the treated surface of Example 1, no seizure wear occurred during the friction test.
[0075] 13 and 14 show, in bar graphs, the average friction coefficients (see FIG. 13) of the treated and untreated surfaces of Example 1 and Comparative Examples 1 and 2, and the time from the start of the friction test to the timing at which the state transitioned to one in which seizure wear occurred (hereinafter referred to as the seizure wear start time, see FIG. 14). Note that the symbol N in FIG. 13 and FIG. 14 indicates the number of times data was acquired, as in FIG. 9 and FIG. 10, and for example, "N=2" means that data was acquired twice.
[0076] As shown in FIG. 13, the average friction coefficient of each treated surface of Example 1 and Comparative Examples 1 and 2 is smaller than the average friction coefficient of the untreated surface, and the average friction coefficient of the treated surface of Example 1 is approximately the same as the average friction coefficient of each treated surface of Comparative Examples 1 and 2.
[0077] However, as shown in Figures 11 and 14, the time to start seizure wear on the treated surface of Example 1 exceeded 30 minutes (1800 seconds), which was too long to measure in this friction test. Also, as shown in Figure 14, the time to start seizure wear on the treated surface of Example 1 was at least five times longer than the time to start wear on the treated surfaces of Comparative Examples 1 and 2. That is, the treated surface of Example 1 achieved a reduction in friction coefficient to the same extent as the treated surfaces of Comparative Examples 1 and 2, while also achieving durability that is more than five times that of the reduction in friction coefficient.
[0078] Thus, the treated surface of Example 1 is less susceptible to seizure wear compared to the treated surfaces of Comparative Examples 1 and 2. This is believed to be because the treated surface of Example 1 has fewer convex portions and deeper indentations on the treated surface compared to the treated surfaces of Comparative Examples 1 and 2, making it less susceptible to seizure wear.
[0079] More specifically, it is believed that, because deep indentations were formed on the treated surface of Example 1, the lubricant held in the indentations was not exhausted during the duration of the friction test (30 minutes), and the supply of lubricant from the indentations to the friction area was not interrupted. Also, in the case of the treated surface of Example 1, the indentations are deep and therefore easily deformed, and the indentations near the friction area repeatedly elastically deform and relax during the friction test, so that the supply of lubricant from the indentations near the friction area to the friction area was continuously performed.
[0080] In this way, in the surface treatment method according to the present embodiment, the particles colliding with the object to be treated as the surface treatment are smaller than those in shot peening, and the moving speed of the particles colliding with the object to be treated during flight is much faster than that in shot peening, so that it is possible to form sparse and deep indentations on the treated surface compared to shot peening. In the treated surface treated by the surface treatment method according to the present embodiment, it is possible to hold a lubricant abundantly in these sparse but deep indentations, which is believed to enable the supply of lubricant to the frictional parts over a long period of time. It is believed that the supply of lubricant to the frictional parts over this long period of time enables the reduction of frictional resistance on the surface and the suppression of wear to be achieved in a manner far superior to that of the prior art.
[0081] In this manner, a surface treatment method that realizes reduction in frictional resistance and suppression of wear on the surface can be provided.
[0082] It should be noted that the embodiments disclosed in this specification are merely examples, and the present invention is not limited to these embodiments, and can be modified as appropriate without departing from the scope of the present invention. [Industrial Applicability]
[0083] The present invention is applicable to a surface treatment method. [Explanation of symbols]
[0084] 1: Injection part 100: Equipment (surface treatment equipment) 11:Support layer 12: Energy absorbing layer 3: Processing object 5:Light source 51:Reflector 53: Condenser lens C: Indentation d1: Thickness d2: Thickness d3: distance L: Laser light P: Particle W: Shock wave
Claims
1. a step of disposing particles on a surface of the energy absorbing layer; an ejection step of ejecting the particles by irradiating a rear surface of the energy absorbing layer with laser light; a flying step of flying the ejected particles toward a processing object; and a collision step of causing the flying particles to collide with the object to be treated.
2. 2. The surface treatment method according to claim 1, wherein in the ejection step, a laser beam is irradiated onto the energy absorbing layer to generate a shock wave, and the particles are ejected by the shock wave.
3. In the disposing step, a plurality of the particles are disposed on a surface of the energy absorbing layer, In the ejection step, a plurality of the particles are ejected, The surface treatment method according to claim 1 , wherein in the collision step, a plurality of the particles are collided with the treatment object.
4. 2. The surface treatment method according to claim 1, wherein the ejection step, the flying step, and the collision step are repeated while changing a position where the particles are collided with the treatment object in the collision step.
5. The surface treatment method according to claim 1 , wherein in the collision step, the particles collided with the object to be treated form depression-shaped impressions on the surface of the object to be treated.
6. The surface treatment method according to claim 5 , wherein the indentation has a depth greater than 0.1 times the diameter of the opening.
7. The surface treatment method according to claim 5 , wherein in the collision step, the particles are collided with the object to be treated so that a protruding valley depth on the surface of the object to be treated is 1 μm or more.
8. 2. The surface treatment method according to claim 1, wherein the particles are made of zirconia, tungsten or high speed steel.
9. 2. The surface treatment method according to claim 1, wherein the particle diameter of the particles is 15 μm or more and 40 μm or less. Law.
Citation Information
Patent Citations
Micro-laser peening treatment using powder and film, and micro-laser peening-treated component
JP2006320907A
Surface treatment method of steel products
JP2018199843A